2015
DOI: 10.3390/ijms161025234
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Cardiovascular Disease Induced by Oxidative Stress

Abstract: Cardiovascular disease (CVD) is the leading cause of morbidity and mortality among patients with diabetes mellitus (DM). DM can lead to multiple cardiovascular complications, including coronary artery disease (CAD), cardiac hypertrophy, and heart failure (HF). HF represents one of the most common causes of death in patients with DM and results from DM-induced CAD and diabetic cardiomyopathy. Oxidative stress is closely associated with the pathogenesis of DM and results from overproduction of reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
255
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(267 citation statements)
references
References 188 publications
(207 reference statements)
2
255
0
10
Order By: Relevance
“…Therefore, avoiding oxidative and inflammatory processes in diabetic patients may help to the prevention of cardiovascular complications. Macrophages generate lipid-laden foam cells due to uncontrolled uptake of modified LDL, especially oxLDL (19). In this sense, feeding the DSF during 6 weeks did not alter plasma oxLDL, indicating that oxidative stress is not increased during the intervention.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, avoiding oxidative and inflammatory processes in diabetic patients may help to the prevention of cardiovascular complications. Macrophages generate lipid-laden foam cells due to uncontrolled uptake of modified LDL, especially oxLDL (19). In this sense, feeding the DSF during 6 weeks did not alter plasma oxLDL, indicating that oxidative stress is not increased during the intervention.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies suggest that hyperglycaemia might trigger oxidative stress resulting in endothelial dysfunction and inflammatory processes that may contribute to CVD development (19). In fact, oxLDL and inflammatory biomarkers are increased in patients with type 2 diabetes (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Persistent hyperglycaemia causes increased production of free radicals as a result of glucose auto-oxidation and protein glycosylation (Lipinski 2001;Asmat et al 2015;Kayama et al 2015). In order to expand treatment options, there is a need to explore the connection between free radicals, hyperglycaemia and diabetes (Oboh et al 2011).…”
Section: In Vitro Antioxidant and α-Amylase Inhibitory Properties Ofmentioning
confidence: 99%
“…Accumulated evidence has suggested that diabetic patients are under oxidative stress, with an imbalance between the free radical generating and radical scavenging capacities [147,148]. 15-LO and XO are peroxidative and prooxidative enzymes, respectively, and sources of ROS [148].…”
Section: Antioxidant Activitymentioning
confidence: 99%